The Role of Digital Technology in Enhancing Human Resource Management in Village Government : A Literature Review - Mikhael Jibrael Balo; Feliks Arfid Guampe; Novi Maryam Lempao; Indra Eka Wardana Toii (Digital Innovation : International Journal of Management, 2024)
Digital transformation in village governance has become a primary strategy for enhancing efficiency and effectiveness in human resource (HR) management. This study aims to analyze the implementation of digital technology in village government HR management and its impact on productivity and administrative efficiency. Employing a systematic literature review method, this research examines implementation trends, success factors, challenges, and optimal strategies for digitalization in HR management at the village level. The findings indicate that the adoption of technologies such as electronic Human Resource Management (e-HRM), cloud computing, and village information systems contributes to faster administration, increased accountability, and optimized performance of village officials. However, challenges remain in technology adoption, including low digital literacy among village officials, limited information and communication technology (ICT) infrastructure, as well as regulatory and policy constraints. To overcome these hurdles, a comprehensive strategy is required, encompassing capacity building through training, strengthening digital infrastructure, and fostering collaboration among central government, village governments, and the private sector. With appropriate policy implementation, the integration of digital technology in village-level HR management can improve public service quality and support more modern and responsive governance.